Penciptaan Karya Film Animasi 2D “Miliv” Dengan Teknik Hybrid - Rafinur Nidiansyah; Arif Sulistiyono; Pandan Pareanom Purwacandra (Institut Seni Indonesia Yogyakarta, 2019)
When human realize that they are not as they appear, it causes personal conflicts in humans, there are two sources that come from inside and outside. With animated films that have become increasingly popular with various groups, the creation of the animated film “MILIV” as one of media delivery in the form of visual and media delivery messages contained in the film.With the concept of hybrid, it combines stopmotion animation techniques, rotoscope, and digital animation, creating an experimental genre animation work with its unique visual style.The animated film “MILIV” tells of a bird who is too late to realize his true identity and is trapped in comfort zone. Contemplation became the main goal in this animated film “MILIV”Keywords: Film, MILIV, Hybrid, Rotoscope, Stopmotion, Experimental, Animation